Impulse Inhibition Ability With Methamphetamine Dependents Varies at Different Abstinence Stages - Liu, Weijun; Tian, Yu; Yan, Xinyu; Yang, Jiemin (Frontiers in Psychiatry, 2021)
Objective: The purpose of this study is to evaluate whether the impulse inhibition ability with methamphetamine dependents would vary at different abstinence stages. Methods: Sixty-three methamphetamine dependents, including 31 short-term (less than 10 months) and 32 long-term (equal to or greater than 10 months) abstinence participants, were recruited for this study. In addition, 33 men were recruited as the healthy control (HC) group. All participants performed a two-choice oddball task, which is well established to assess impulse inhibition. Accuracy for deviant trials and deviant−standard reaction time (RT) delay were computed as indexes of impulse inhibition. Results: The accuracy for deviant trials was significantly decreased in short-term abstinence subjects (90.61%) compared to HC subjects (95.42%, p < .01), which was coupled with a shorter RT delay reflecting greater impulsivity in the short-term group vs. the HC group (47 ms vs. 73 ms, p < .01). However, impulse inhibition was improved in the long-term group, shown by the increased accuracy for deviant trials in the long-term group compared to the short-term group (94.28% vs. 90.61%, p < .05) and the similar accuracy for the long-term and HC groups (p > .05). Further regression analyses confirmed that the abstinence duration positively predicted impulse inhibition of methamphetamine dependents, both in accuracy and RT for deviant stimulus (β = .294, p = .019; β = .337, p = .007). Conclusion: These results suggest that long-term abstinence is more effective in improving impulse inhibition with methamphetamine dependents.